High-temperature proton exchange membrane fuel cell membrane electrode and preparation method thereof - ZHANG YUFENG; ZHANG XUELIN; LIU XIAOWEI; TUO YANJING (2015)
The invention discloses a high-temperature proton exchange membrane fuel cell membrane electrode and a preparation method thereof. The membrane electrode is composed of an anode diffusion layer, an anode catalysis layer, a proton exchange membrane, a cathode catalysis layer and a cathode diffusion layer, wherein the anode catalysis layer and the cathode catalysis layer are each formed by mixing graphene aerogel, PTFE and catalyst. The graphene aerogel is a low-density solid material and has high specific surface area, rich nano-porous structure, high conductivity and hydrophobic property. Due to the catalysis layers with the graphene aerogel phosphoric acid molecules in the proton exchange membrane can be effectively restrained from being adsorbed by the surfaces of the catalysis layers, phosphoric acid is prevented from loss, and the service life of the proton exchange membrane is prolonged; meanwhile, due to the high conductivity of the graphene aerogel, the ohmic resistance of the membrane electrode can be reduced, and therefore the output power of a high-temperature proton exchange membrane fuel cell is improved.